1984
DOI: 10.1017/s0014479700000958
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of Different Techniques for Inoculating Phaseolus vulgaris with Rhizobium

Abstract: A technique to better ensure reliable nodulation of pot-grown, P. vulgaris plants with cultured strains of Rhizobium is described. Nodulation, dinitrogen fixation (acetylene reduction) activity and growth of 28-day-oId plants were all stimulated markedly when seeds had been inoculated with culturedRhizobium phaseoli suspended in alginate gel (Agrigel) rather than in sucrose solution. Nodulation attributes of plants inoculated with R. phaseoli strain RCR 3644 which had been sub-cultured repeatedly on yeast mann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…In contrast, the more rigid structure and the high viscosity of the sodium alginate 2 polymers may have influenced the response (Zimmermann et al 2007). Rawsthorne & Summerfield (1984) obtained similar results in studies that showed an increased nitrogen fixation and higher nodule dry weights using alginate gel compared to controls.…”
Section: Discussionsupporting
confidence: 65%
“…In contrast, the more rigid structure and the high viscosity of the sodium alginate 2 polymers may have influenced the response (Zimmermann et al 2007). Rawsthorne & Summerfield (1984) obtained similar results in studies that showed an increased nitrogen fixation and higher nodule dry weights using alginate gel compared to controls.…”
Section: Discussionsupporting
confidence: 65%
“…Gelatinous substances previously have been used as carriers for rhizobia (3,11,13,18). Advantages of gels include the protection of microorganisms from desiccation and good microorganism-seed contact (13,16).…”
mentioning
confidence: 99%
“…The gels used in these previous studies, however, were not of a fluid consistency during seed inoculation and were not used in conjunction with fluid drilling. Pot-grown dwarf french (field) beans were successfully inoculated with R. phaseoli by using a wet alginate gel (18). Field beans inoculated with R. phaseoli in an alginate gel during fluid drilling had more nodules per plant 28 days after sowing than did beans inoculated with a peat carrier (11).…”
mentioning
confidence: 99%